Ability of keratinase Bacillus megaterium UKM B 5710 to cleave different types of keratin substrates - Avdiiuk, K.V.; Varbanets, L.D. (Problems of Environmental Biotechnology, 2023)
The purpose of our work was to investigate the ability of Bacillus megaterium UKM B-5710 to break down various keratin substrates: black and white chicken feathers, white turkey feathers, parrot feathers of different colors, sheep's wool, pig bristles, children's hair and nails, which were added to the composition of the nutrient medium as the only source of carbon and nitrogen.